2017
DOI: 10.21511/ppm.15(2).2017.02
|View full text |Cite
|
Sign up to set email alerts
|

Does board composition have an impact on CSR reporting?

Abstract: Corporate social responsibility (CSR) reporting plays a key role in management control, particularly in light of the increased demand for non-financial reporting after the financial crisis of [2008][2009]. This literature review evaluates 47 empirical studies that concentrate on the influence of several board composition variables on the quantity and quality of CSR reporting. The author briefly introduces the research framework that underpins current empirical studies in this field. This is followed by a discu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
52
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(56 citation statements)
references
References 26 publications
(24 reference statements)
2
52
0
2
Order By: Relevance
“…The number of board meetings, denoted by Nmeeting , is a common variable used in empirical research (Velte, ) as a proxy for board activity. A higher activity might lead to greater attention to CSR problems and could therefore facilitate a correct response to the company's negative social and environmental impact.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The number of board meetings, denoted by Nmeeting , is a common variable used in empirical research (Velte, ) as a proxy for board activity. A higher activity might lead to greater attention to CSR problems and could therefore facilitate a correct response to the company's negative social and environmental impact.…”
Section: Methodsmentioning
confidence: 99%
“…Some of them found a negative relationship between gender diversity and CSR performance (Darus, Isa, Yusoff, & Arshad, ; Fauzi & Locke, ; Majeed, Aziz, & Saleem, ), whereas others found no significant link (Jhunjhunwala & Mishra, ). However, most of them proved that increasing female representation in management positions has a positive influence on CSR performance (Ben‐Amar et al, ; Ciocirlan & Pettersson, ; Dienes & Velte, ; Fernandez‐Feijoo, Romero, & Ruiz‐Blanco, ; Francoeur et al, ; Kyaw et al, ; Liao, Luo, & Tang, ; Liao, Zhang, & Wang, ; Wu, Guang, Xu, & Wang, ), as shown by recent meta‐analysis (Rao & Tilt, ; Velte, ).…”
Section: Literature Review and Research Hypothesesmentioning
confidence: 98%
“…Frequency of board meeting is used as a common proxy to measure board activity (Velte, 2017). In financial industry like banking sector, it is not clear whether board activity influences CSR reporting.…”
Section: Board Activitymentioning
confidence: 99%
“…in CSR research (Velte, 2017). But board expertise can be logically linked with CSR strategy formulation and implementation.…”
Section: Board Expertisementioning
confidence: 99%
See 1 more Smart Citation